Narrativas frente a la modificación del proyecto de vida y las relaciones interpersonales del cuidador informal según las fases de la enfermedad de Alzheimer (2024)
This research aimed to describe the narratives surrounding the modification of life projects and interpersonal relationships among a group of informal caregivers of individuals in various stages of Alzheimer's disease. The study was conducted within a qualitative methodological framework, utilizing a narrative design with a descriptive scope.The population consisted of ten informal caregivers of people with Alzheimer's, residing in Bogotá, who participated in three focus groups through unstructured interviews.